2018
DOI: 10.2147/cmar.s179043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic values of the mRNA expression of excision repair cross-complementation enzymes in hepatitis B virus-related hepatocellular carcinoma

Abstract: BackgroundThe current study aims at using the whole genome expression profile chips for systematically investigating the diagnostic and prognostic values of excision repair cross-complementation (ERCC) genes in hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC).Materials and methodsWhole genome expression profile chips were obtained from the GSE14520. The receiver-operating characteristic (ROC) curve, survival analysis, and nomogram were used to investigate the diagnostic and prognostic values of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…28,29 According to several studies, patients with low expression of ERCC4 were associated with worse overall survival in hepatocellular carcinoma. 30 Our study also highlighted that OS patients with low expression of ERCC4 have displayed worse survival outcome of the patients (Figure 3(a)).…”
Section: Discussionsupporting
confidence: 56%
“…28,29 According to several studies, patients with low expression of ERCC4 were associated with worse overall survival in hepatocellular carcinoma. 30 Our study also highlighted that OS patients with low expression of ERCC4 have displayed worse survival outcome of the patients (Figure 3(a)).…”
Section: Discussionsupporting
confidence: 56%
“…However, latest studies showed that such a silent mutation may affect gene expression, protein levels, and can also modify the structure and functionality of proteins [61]. Moreover, ERCC2 expression levels may be used to distinguish between HBV-related HCC tumor and paracancerous tissues [62], which confirms its role in HBV-related liver damage. Moreover, HBV can modulate DNA damage by inhibiting several DNA damage response proteins, including ERCC2, through viral HBx [63].…”
Section: Discussionmentioning
confidence: 91%